Sexual Function in Patients Treated With Stereotactic Radiotherapy For Prostate Cancer: A Systematic Review of the Current Evidence. Issue 9 (11th July 2019) - Loi, Mauro; Wortel, Ruud C.; Francolini, Giulio; Incrocci, Luca
ABSTRACT: Introduction: Sexual function can be impaired by all prostate cancer treatment modalities, but studies specifically addressing the impact of stereotactic body radiotherapy (SBRT) on sexual function are scarce. Aim: To systematically evaluate sexual outcomes in patients treated by SBRT for prostate cancer and determine clinical factors associated with erectile dysfunction (ED). Methods: A systematic review of the available literature was performed on PubMed/Medline, Scopus, and Cochrane Library databases in June 2017 according to the Preferred Reporting Items for Systematic Review and Meta-analysis statement. Only articles providing data on baseline and post-treatment sexual function after SBRT (≥5 Gy/fraction) were included in this analysis (n = 12). Main Outcome Measure: Sexual function deteriorates after SBRT of the prostate. Results: Deterioration of sexual health was found, with Expanded Prostate Cancer Index Composite–26 sexual domain scores showing a median decrease of 9.2 at 12 months and a median decrease of the Sexual Health Inventory for Men subdomain score by 2.7 at 12 months (from baseline median value of 56.3 and 16, respectively). At 60 months, ED was reported by 26–55% of previously sexually functioning patients in 5 of the 12 studies. Clinical Implications: ED affects ≤55% of previously sexually functioning patients at 5 years, as reported for other non-surgical treatment modalities. Strengths & Limitations: This study enforced strict inclusion criteria of selected studies and exclusion of patients receiving concurrent androgen deprivation therapy. However, inconsistencies in the choice of assessment tool and definition of ED hamper a robust meta-analysis of pooled data. Conclusion: Sexual function decline after SBRT for prostate cancer appears to be similar to other modalities and should be specifically addressed in future studies.